Isolation, identification and diesel-oil biodegradation capacities of indigenous hydrocarbon-degrading strains of Cellulosimicrobium cellulans and Acinetobacter baumannii from tarball at Terengganu beach, Malaysia - Nkem, Bruno Martins; Halimoon, Normala; Md Yusoff, Fatimah; Wan Johari, Wan Lufti; Zakaria, Mohamad Pauzi; Medipally, Srikanth Reddy; Kannan, Narayanan (Elsevier, 2016)
In this study, we isolated two indigenous hydrocarbon-degrading bacteria from tarball found in Rhu Sepuluh beach, Terengganu, Malaysia. These bacteria were identified based on their physiological characteristic and 16S rRNA gene sequence analysis, and they showed 99% similarity with Cellulosimicrobium cellulans DSM 43879 and Acinetobacter baumannii ATCC 19606 respectively. Their hydrocarbon-degrading capabilities were tested using diesel-oil as sole carbon source. Results analysed using GC–MS, showed diesel-oil alkanes were degraded an average 64.4% by C. cellulans and 58.1% by A. baumannii with medium optical density reaching 0.967 (C. cellulans) and 1.515 (A. baumannii) in minimal salt media at 32 °C for 10 days. Individual diesel-oil alkanes were degraded between 10%–95.4% by C. cellulans and 0.2%–95.9% by A. baumannii. Both strains utilized diesel-oil for growth. The study suggests both strains are part of indigenous hydrocarbon-degrading bacteria in tarball with potential for bioremediation of oil-polluted marine environment.